INNOVATIVE METHODS FOR DEVELOPING ANALYTICAL COMPETENCE IN HIGHER EDUCATION (Bulletin of Innovative Research, 2026)
This paper investigates innovative methods used in higher education to develop students' analytical competence. It focuses on flipped classrooms, project-based learning, digital simulations, learning analytics, and COIL, demonstrating how these approaches foster critical thinking and data analysis skills. Empirical studies and practical strategies are discussed to highlight their effectiveness.